PERANAN SATUAN POLISI PAMONG PRAJA DALAM MENERTIBKAN GELANDANGAN DAN PENGEMIS (GEPENG) DI KOTA DUMAI - Simorangkir, Landra Julianto; Firdaus, Emilda; Zulwisman, Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The state, through its government, both central and regional, is obliged to deal with street children, homelesspeople and beggars as the government's responsibility in the field of welfare according to the 1945Constitution of the Republic of Indonesia, who are called homeless people and beggars. In the context ofadministering regional government in accordance with the mandate of the Constitution, controlling homelesspeople and beggars in the city of Dumai is carried out by the Civil Service Police Unit. So the aim of thisresearch is to find out the role of the Civil Service Police Unit in curbing vagrants and beggars (Gepeng) inDumai City and to find out what obstacles are faced by the Civil Service Police Unit in curbing vagrants andbeggars in Dumai City and also to find out the efforts made. must be carried out by the regional government incontrolling homeless people and beggars.The research method in this thesis uses a type of sociological juridical research, namely a researchapproach that emphasizes the legal aspects relating to the main issues to be discussed, linked to the reality inthe field. This research was conducted at the Dumai City Social Service and Satpol PP. The data sources usedare primary data and secondary data, data collection techniques in this research are observation, interviewsand literature reviewBased on research results, the role of the Civil Service Police Unit in controlling homelesspeople and beggars in Dumai City has not been implemented well, because of the gap between legalregulations and what is happening in the field. The inhibiting factors are budget factors, facilities andinfrastructure factors, and human resource factors. The efforts made by the Dumai City Government throughthe Civil Service Police Unit to control homeless people and beggars are efforts that have been made by theDumai City Government.Keyword: Homeless, Beggar, Dumai.